2012
DOI: 10.5935/1678-9741.20120015
|View full text |Cite
|
Sign up to set email alerts
|

Dreno pleural subxifoide confere menor comprometimento da força muscular respiratória, oxigenação e menor dor torácica após cirurgia de revascularização do miocárdio sem circulação extracorpórea

Abstract: Dreno pleural subxifoide confere menor comprometimento da força muscular respiratória, oxigenação e menor dor torácica após cirurgia de revascularização do miocárdio sem circulação extracorpórea: estudo controlado randomizado Subxyphoid pleural drain confers lesser impairment in respiratory muscle strength, oxygenation and lower chest pain after off-pump coronary artery bypass grafting: a randomized controlled trial Abstract Objective: To evaluate respiratory muscle strength, oxygenation and chest pain in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
5
1
5
Order By: Relevance
“…xiphoid position with lower intensities of pain and dyspnea, [14][15][16]18 we did not observe any differences between the groups regarding the subjectively assessed degrees of dyspnea and pain. The shorter time for which the pleural drain was used in the lateral group may have influenced these results.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…xiphoid position with lower intensities of pain and dyspnea, [14][15][16]18 we did not observe any differences between the groups regarding the subjectively assessed degrees of dyspnea and pain. The shorter time for which the pleural drain was used in the lateral group may have influenced these results.…”
Section: Discussioncontrasting
confidence: 48%
“…The sample size calculation was performed using the WinPepi software for Windows. Based on data from a previous randomized trial that assessed maximal respiratory pressures among patients undergoing CABG surgery, 16 we found that we would need a sample size of 20 participants in each group to find a difference in predicted percentage for MIP of 14% between the groups, considering standard deviations of 15% both in group 1 and in group 2, a study power of 80%, and an alpha level of 0.05.…”
Section: Sample Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pleural drain insertion through intercostal space promotes higher thoracic trauma, increased pain and discomfort for the patient, leading to increased vulnerability to lung complications. In patients without COPD undergoing off-pump CABG (OPCAB), the shift of pleural drain insertion to subxyphoid region reduces postoperative pulmonary dysfunction [ 6 , 7 ] . Our hypothesis is that reducing thoracic trauma in COPD patients underwent OPCAB could determine lower impairment to the lung function and better clinical results.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous research, due to the multifactorial impairment of pulmonary function [5,19-23] , there is a significant risk of respiratory complications during the postoperative period, which may result in prolonged time of mechanical ventilation, longer postoperative hospital stay, and possibly death [5,20,21] . Those results are in agreement with our findings; the CMV and L-OLS groups with greater pulmonary function impairment also showed a significantly greater intubation time and hospital stay in comparison to the E-OLS group.…”
Section: Discussionmentioning
confidence: 99%